Water cortisol and testosterone in Nile tilapia (Oreochromis niloticus) recirculating aquaculture systems - Mota, Vasco (2019)
The accumulation of steroids released by fish in recirculating aquaculture systems (RAS) may potentially influence their physiology and behavior. The present study examined the release rate of cortisol and testosterone by Nile tilapia, Oreochromis niloticus, and their accumulation in six identical lab scale RAS operated at different water exchange rates (150 L/kg feed/day, (LowRAS) and 1500 L/kg feed/day, (HighRAS)) and how steroid accumulation is affected by grading and weighing induced stress. Water cortisol and testosterone concentrations during the experimental period ranged between 1.0 and 5.1 ng/L and between 1.4 and 9.4 ng/L, respectively. Water cortisol concentration was 34% and 43% significantly higher in LowRAS when compared with HighRAS at week 3 and week 4, whereas for water testosterone concentration the two treatments did not differ. Overall steroid release rates were 0.02 +/- 0.02 and 0.04 +/- 0.02 ng/g body weight/h for cortisol and testosterone, respectively. Two hours after grading and weighing water cortisol concentration increased 30% in the LowRAS whereas water testosterone concentration remained unchanged. Calculated cortisol and testosterone discharge from the system were, respectively, 87% and 89% lower in LowRAS than in HighRAS. These findings show that reduced water usage and acute stressors can induce significant accumulation of cortisol in the rearing water at levels close to olfactory detection. Accumulation of metabolites, in particular steroids, should be taken in consideration when designing and managing RAS to prevent exceeding allowable concentrations. Statement of relevance: RAS containing Nile tilapia, cortisol and testosterone are released to the culture water. Water cortisol concentration depends on the water exchange rate that is used and higher concentrations are expected in lower water exchange rates. Fish grading and weighing has a short-term effect on the water cortisol concentrations, after which concentrations return to the basal levels. These findings show that reduction in water usage and fish handling may lead to a significant increase of hormones in the rearing water, which emphasizes the importance of accounting for steroids in the design and management of RAS. (C) 2016 Elsevier B.V. All rights reserved.